Sub-micrometre accurate free-form optics by three-dimensional printing on single-mode fibres - Timo Gissibl (Nature Portfolio, 2016)
Combining freeform optics with micro- and nano-optics can permit wavefront shaping, phase engineering, k-space and polarization control. Here, Gissibl et al. use femtosecond 3D printing to manufacture free-form optical elements, giving sub-micrometre accuracy so that direct manufacturing on single-mode fibres is possible.